A inspetoria da instrução pública maranhense (1843-1889) - COELHO, Josivan Costa (2017)
We analyze the action of the province of public education, an organ created in 1843 with the in charge of supervising public education in the province of Maranhão. The study period that corresponds to its creation until 1889 and its objectives were to elucidate the structure of the identify the inspectors and delegates who worked during the analyzed period, analyze the actions carried out in the management of the inspectors who, for the longest time, Province. Documentary sources in the survey were the crafts, reports and regulations formulated by provincial presidents, by the inspectors of public instruction, by delegates literary, by public teachers, among others. The documentation used is stored in the Public Archive of the State of Maranhão and in the Benedito Leite State Library. At bibliographical data used to analyze the historiographic production of responsible for supervising public education in the national territory were Marcílio (2006), Borges (2008), Miranda (2012), Nery (2013), Santos (2017), among others. The New Story Cultural subsidized the analysis through its theoretical and methodological assumptions. Were institutions linked to the province, such as: Literary Public Instruction, Medical Board. We also show the trajectory of the inspectors time they occupied the position or that they had position of prominence in the local and national politics, being elected Francisco Sotero dos Reis, José da Silva Maia and Augusto Olimpio Gomes de Castro. The investigation pointed out that the institution throughout the period controlled the teacher, nominated and dismissed literary delegates, recommended the adoption of textbooks, organized selective processes for the hiring of teachers, established standards for the public and private education, among many other tasks. The analysis also showed that teachers and students did not simply taxation, but circumvented the impositions of regulatory institutions through numerous tactics.